Analisis Multiaspek Keberlanjutan Usahatani Padi Gogo di Provinsi Gorontalo - Tahir, Nur Safitri; Nai, Putri Muhriyanti; Kasim, Nitam; Lasena, Mirda; Ladiku, Sri Rahmawati (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Rice farming plays an important role in supporting food security, especially in dryland areas such as Gorontalo Province. This study aims to evaluate the sustainability of rice farming using a Multi-aspect Sustainability Analysis (MSA) approach, covering environmental, economic, social, and farm management aspects. Data were collected through in-depth interviews and structured questionnaires involving government officials and agricultural experts from the BSIP Gorontalo in two districts. The results show that overall, the sustainability of rice farming is categorized as Low Sustainable with an average validation score of 37.07. The environmental dimension received the highest score (46.7), while the social and management aspects showed the lowest performance (21.08), which falls under the Unsustainable category. Sensitivity analysis identified 25 key factors influencing sustainability, including the stability of rice prices, the use of agricultural waste, family participation, and communal efforts in rice field management. To improve the sustainability of rice farming, strategic interventions are needed, such as optimizing natural resource management, enhancing farmers' capacity, and strengthening social and economic governance. The implementation of sustainability-based policies is expected to support the overall development of the rice farming sector and contribute to food security in Gorontalo Province.